Evaluation of Cardiovascular Concerns of Intravenous Lacosamide Therapy in Epilepsy Patients - Lu, Yan-Ting; Lin, Chih-Hsiang; Ho, Chen-Jui; Hsu, Che-Wei; Tsai, Meng-Han (Frontiers in Neurology, 2022)
Objective: Voltage-gated sodium channels (VGSCs) play an important role in neuronal excitability and epilepsies. In addition to the brain, VGSCs are also abundant enriched in cardiac tissues and are responsible for normal cardiac rhythm. Theoretically, sodium channel blocking antiseizure medications (SCB-ASMs) may have unwanted cardiac side effects. Lacosamide (LCM) is increasingly used in patients with status epilepticus (SE) due to the availability of intravenous formula. The concerns about the proarrhythmic effect are even higher due to the need for rapid administration of LCM. There were limited data on the cardiac safety of intravenous LCM. Hereby, we performed a study to observe the effect of intravenous loading of LCM in patients with seizures in our Neurological Intensive Care Unit (NICU). Methods: We retrospectively reviewed the patients using parenteral LCM for seizures in NICU. A routine infusion time of 30 minutes was performed. The electrocardiogram (ECG) and blood pressure were recorded before and after LCM injection. Results: We retrospectively reviewed the clinical data of 38 patients using LCM for treating seizures. Two patients had cardiac side effects after LCM loading, one (3.0%) with new-onset first-degree AV block and the other (3.0%) with atrial premature complex. For the quantitative changes of ECG parameter analysis, there was no change in QRS complex, corrected QT intervals, and heart rate except that the PR interval was mildly increased. A mild decrease in the diastolic blood pressure and mean arterial pressure were also observed. None of the above-mentioned parameter alterations required clinical intervention. Conclusion: We evaluated the cardiac safety concern in real-world epilepsy patients requiring intravenous LCM. Near half of this cohort responded to LCM therapy and there was no life-threatening cardiac adverse effect. Intravenous LCM does have some effects on the ECG parameters and blood pressure but without clinical relevance. Despite the theoretical concern of cardiac adverse effects of LCM, the benefit of seizure control outweighed the risk in patients with status epilepticus or seizure clusters, such as hyperthermia, pulmonary edema, cardiac arrhythmias, or cardiovascular collapse.